A specific warm up improves kayak ergometer performance in trained athletes - Bishop, D.; Bonetti, D.; Spencer, M. (2000)
Warm up (WU) exercise is a generally accepted practice to improve supramaximal performance. This has been attributed to faster VO2 kinetics consequent to the residual metabolic acidemia. However, we have previously shown that the metabolic acidemia induced by a continuous WU (CWU) at the anaerobic threshold (AnT) decreases supramaximal performance via an impaired anaerobic contribution. The purpose of this study was to determine if a specific WU (SWU) could speed VO2 kinetics, without reducing the anaerobic contribution, and thus improve supramaximal performance. Seven experienced male paddlers volunteered for this study. In the initial testing session, each athlete performed a step test to determine peak VO2 and thresholds. In a random, counterbalanced order, subjects then performed the CWU or SWU followed by a 2-min, all-out kayak ergometer test. The CWU consisted of 15 min of exercise half way between their aerobic threshold (AeT) and their AnT. The SWU was identical except that the last 5min was replaced with 5, 10-s sprints at 200% peak VO2, separated by 50s of recovery at the AeT. A repeated-measures, one-way ANOVA was used to detect significance (P<0.05). There was a significantly greater peak power (629.0 v 601.2 W) and average power (327.6 v 321.3 W) following the SWU. There was no significant difference between peak VO2, total VO2 or AOD. The blood lactate concentration was significantly greater following the SWU. Although not significant, there was a tendency for faster VO2 kinetics following the SWU (Fig 1). The results of this study indicate that 2-min kayak ergometer performance is significantly greater following a SWU than a CWU. It is possible that a SWU improves supramaximal performance by priming the aerobic system without causing too great an acid-base disturbance. (2000 Pre-Olympic Congress, Sports Medicine and Physical Education, International Congress on Sport Science, 7-13 September - Brisbane, Australia 2000)